2008
DOI: 10.1002/mds.22290
|View full text |Cite
|
Sign up to set email alerts
|

Parkinsonism and dystonia caused by the illicit use of ephedrone—A longitudinal study

Abstract: A neurological syndrome characterized by levodopa unresponsive bradykinesia, retropulsion with falls backwards, dysarthria, gait disturbance, dystonia, and emotional lability was identified in 13 male opiate addicts following the prolonged intravenous use of ephedrone (methcathinone), a central nervous stimulant prepared from pseudoephedrine, potassium permanganate, and vinegar. The natural history, response to treatment, and clinical features has been studied, and MR and dopamine transporter SPECT brain imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
88
3
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 27 publications
6
88
3
3
Order By: Relevance
“…Several studies (Discalzi et al 2000;Herrero Hernández et al 2003;Herrero Hernandez et al 2006;Ky et al 1992;Ono et al 2002;Penalver 1957) have showed that CaNa2EDTA is clinically effective in the treatment of overt manganism in humans. These observations are consistent with recent therapeutic success in a severe case of genetic hypermanganesemia with extrapyramidal syndrome, polycythemia, and hepatic cirrhosis (Tuschl et al 2008) and possibly in ephedrone-manganic syndrome cases (Selikhova et al 2008). Early studies lacked detailed information on treatment and biomarkers, and other drugs were coadministered, thus potentially confounding the results.…”
Section: Treatmentsupporting
confidence: 78%
“…Several studies (Discalzi et al 2000;Herrero Hernández et al 2003;Herrero Hernandez et al 2006;Ky et al 1992;Ono et al 2002;Penalver 1957) have showed that CaNa2EDTA is clinically effective in the treatment of overt manganism in humans. These observations are consistent with recent therapeutic success in a severe case of genetic hypermanganesemia with extrapyramidal syndrome, polycythemia, and hepatic cirrhosis (Tuschl et al 2008) and possibly in ephedrone-manganic syndrome cases (Selikhova et al 2008). Early studies lacked detailed information on treatment and biomarkers, and other drugs were coadministered, thus potentially confounding the results.…”
Section: Treatmentsupporting
confidence: 78%
“…In a follow-up survey of 34 individuals initially discussed with a poisons center in Israel following use of "Hagigat" capsules, which contain cathinone, common unwanted effects included gastrointestinal (nausea, vomiting, diarrhea), cardiovascular (tachycardia, hypertension), neurological (headache, restlessness, anxiety), and respiratory (dyspnea) [13]. There have been numerous reports of "parkinsonism" like neurological toxicity developing following intravenous injection of "Russian Cocktail" across Russia and a number of former Eastern European countries [16][17][18][19][20][21][22]. These individuals had been injecting methcathinone, and initially it was thought that their symptoms directly related to this.…”
Section: Discussionmentioning
confidence: 99%
“…These individuals had been injecting methcathinone, and initially it was thought that their symptoms directly related to this. However, on further investigation and detailed toxicological analysis, it was found that the solutions being injected had high concentrations of manganese and that, in fact, the extrapyramidal features were related to manganese toxicity [16][17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there have been a number of reports, primarily originating from Eastern European countries and Russia, of young addicts afflicted with an atypical form of parkinsonism (de Bie et al 2007;Meral et al 2007;Sanotsky et al 2007;Selikhova et al 2008;Sikk et al 2007;Stepens et al 2008;Varlibas et al 2009) (Table 1). This form of parkinsonism is the result of intravenous injections of a psychostimulant drug called "ephedrone" or "Russian cocktail," a drug in which ephedrine is oxidized using potassium permanganate and acetic acid (Sanotsky et al 2007;Stepens et al 2008).…”
Section: Mn-induced Parkinsonism From Human Conditions Not Related Tomentioning
confidence: 99%
“…mate is used as the oxidizing agent rather than potassium permanganate (Selikhova et al 2008;Stepens et al 2008). The most parsimonious explanation is that Mn is the causative agent in this atypical form of parkinsonism.…”
Section: Mn-induced Parkinsonism From Human Conditions Not Related Tomentioning
confidence: 99%